Controlling externalities in the presence of rent seeking - Ian A. MacKenzie (ETH Zurich, CER-ETH - Center of Economic Research, 2009)
Contests are a common method to describe the distribution of many different types of rents. Yet in many of these situations the utilisation of the prize plays an important role in determining agents payoffs and incentives. In this paper, we investigate the incentives to expend effort for a prize that produces consumption externalities and consider alternative regulatory policies. We find relatively more global consumption externalities will increase (decrease) rent seeking when con- sumption externalities are negative (positive). We show how introducing Pigouvian taxation (possibly with revenue transfer) and Coasean bargaining alters equilib- rium effort and payoffs. Pigouvian taxation tends to reduce both effort and payoffs whereas this is not always the case for Coasean bargaining. In the presence of suf- ficiently large consumption externalities, establishing Pigouvian taxation coupled with some element of lump-sum transfer may reduce costly rent seeking effort and improve the welfare of some agents compared to other approaches.
Keywords: C72; D63; D62; D31; Q53; 330; externalities; contest; natural resources; Rent-Seeking; Externer Effekt; Natürliche Ressourcen; Verhandlungstheorie; Spieltheorie; Theorie